The Impact of the Covid-19 Pandemic on Polish IT Enterprises - Financial Sector Analysis - Goldmann, Katarzyna; Zawadzki, Aleksander (Copernican Journal of Finance & Accounting, 2024)
The subject of this article is a financial sector analysis of companies operating in the IT industry whose shares are listed on the main and parallel markets of the Warsaw Stock Exchange. The analysis period covers the years 2018-2022, which includes the period of the COVID-19 pandemic. Opinions vary regarding the impact of the pandemic on the activities of the described industry. The aim of the article is to assess the impact of the Covid-19 pandemic on the financial situation of IT enterprises. The authors put forward 4 theses in the article: two regarding the impact of the pandemic on the financial situation of the examined industry, one stating the difference in the financial situation of companies listed on the primary and parallel markets (NC) and one stating the increase in the investment attractiveness of companies from the IT sector. The financial sector analysis of the IT industry in 2018-2022 allowed us to determine general trends in given analytical areas and confirm the theses. The determined statistical parameters show that the COVID-19 pandemic had a positive impact on the financial situation of IT sector companies listed on the Stock Exchange. The changes apply to most of the analyzed enterprises. The obtained results indicate differences in the financial situation of IT sector companies listed on the main market compared to the parallel market and an increase in the investment attractiveness of IT sector companies in the analyzed period. This article is a starting point for further research in the field of IT sector analysis, including determining or changing the market position of individual enterprises.